Endocrine Disturbances in Polycy'stic Ovary Sy'ndrome - Siddiq Ahmed, Aydin; Haqqi Tahir, Pinar (Tikrit Journal of Pharmaceutical Sciences, 2023)
Polycystic ovary syndrome (PCOS) is a heterogeneous disorder of unknown aetiology affecting 5-10% of women of reproductive age. It is a disorder that affects the reproductive, endocrine and metabolic systems, and it is the most common cause of anovulatory infertility. The purpose of this study is to nvestigate the endocrine disturbance in PCO. Two hundred infertile women attended Infertility Unit in Kirkuk were subjected to this study. Their ages range between 17 and 47 years (30.5 + 6.89) with average duration of infertility at the time of the study was (7.23 year + 4.60). Twenty volunteer healthy fertile women of same age range as subjected infertile patients, with no clinical evidence of endocrine abnormalities were subjected to the study as a control group. The immunoradiometric assay of the follicle simulating hormone (FSH), luteinizing hormone (LH), LH: FSH ratio, prolactin and progesterone hormones were carried out on samples obtained fro each individual. Regarding the endocrinal evaluation in PCOS cases, our results revealed that mean values of serum LH, FSH and prolactin levels were significantly (P<0.05) elevated in most women who showed PCO and they reached 35.79 U/L + 5.366 ,15.89 IU/L + 4.228 and 21.84 ng/L + 9.534. LH:FSH ratio also showed a significant (p<0.03) increase in this group when compared with that of control group and reached 2.49 = 1.12 in infertile women with PCO. Mean value of serum progesterone level was significantly decreased in those women and declined to 0.14 ng/L £0.214 Regarding the age of women, most cases of PCOS were at age groups 20-29 and 30-39 years which comprised 44.87 % of the 156 cases.